Synthetic image modalities generated from matched CT and MRI data: a new approach for using MRI in brachytherapy - Krempien, Robert; Grabowski, Hartwig A.; Harms, Wolfgang; Hensley, Frank W.; Haßfeld, Stefan; Mende, Ulrich; Treiber, Martina; Wannenmacher, Michael (Medical image computing and computer assisted intervention - MICCAI '99, 1999)
Target definition and dosimetric evaluation of brachytherapy procedures is crucial in developing proper technique and has prognostic implications. Accurate definition of tumour volume and organs at risk is essential for treatment planing. CT accurately localise sources, but often poorly delineates tumour volume. Magnetic resonance imaging (MRI) has introduced several imaging benefits such as improved soft tissue definition and unrestricted multiplanar and volumetric imaging. However, MRI has not yet seriously challenged CT for brachytherapy planing in most sites. One main reasons for this is the poor imaging of the applicator dummy markers required for detecting the source dwell positions. Therefore a new system generating synthetic image modalities from matched and fused CT and MRI-data has been developed.
Gesehen am 16.03.2021